Insights into interaction mechanism of inhibitors E3T, E3H and E3B with CREB binding protein by using molecular dynamics simulations and MM-GBSA calculations. Issue 3 (4th March 2021) - Wu, S.L.; Zhao, J.; Sun, H.B.; Li, H.Y.; Yin, Y.Y.; Zhang, L.L.
ABSTRACT: CREB binding protein (CBP) and its paralog E1A binding protein (p300) are related to the development of inflammatory diseases, cancers and other diseases, and have been potential targets for the treatment of human diseases. In this work, interaction mechanism of three small molecules E3T, E3H, and E3B with CBP was investigated by employing molecular dynamics (MD) simulations, principal component analysis (PCA), and molecular mechanics/generalized born surface area (MM-GBSA) method. The results indicate that inhibitor bindings cause the changes of movement modes and structural flexibility of CBP, and van der Waals interactions mostly drive associations of inhibitors with CBP. In the meantime, the results based on inhibitor-residue interactions not only show that eight residues of CBP can strongly interact with E3T, E3H and E3B but also verify that the CH-CH, CH-π, and π-π interactions are responsible for vital contributions in associations of E3T, E3H and E3B with CBP. In addition, the H-O radial distribution functions (RDFs) were computed to assess the stability of hydrogen bonding interactions between inhibitors and CBP, and the obtained information identifies several key hydrogen bonds playing key roles in bindings of E3T, E3H and E3B to CBP. Potential new inhibitors have been proposed.